Modeling of melting process in a single screw extruder for polymer processing - Ihor Mikulionok (Eastern-European Journal of Enterprise Technologies, 2018)
We developed a mathematical model of the melting zone of a single-screw extruder for processing of polymers. The model takes into account a heat transfer of a polymer with a worm and a cylinder of an extruder (parameters of a heat transfer agent in the worm, as well as parameters of a heat carrier or electric heaters on the outer surface of the cylinder), as well as the real boundary conditions (the worm rotates, the cylinder is fixed).